Structural analysis of the putative SARS-CoV-2 primase complex - Konkolova, Eva; Klima, Martin; Nencka, Radim; Boura, Evzen (Journal of structural biology, 2020)
We report the crystal structure of the SARS-CoV-2 putative primase composed of the nsp7 and nsp8 proteins. We observed a dimer of dimers (2:2 nsp7-nsp8) in the crystallographic asymmetric unit. The structure revealed a fold with a helical core of the heterotetramer formed by both nsp7 and nsp8 that is flanked with two symmetry-related nsp8 β-sheet subdomains. It was also revealed that two hydrophobic interfaces one of approx. 1340 Å2 connects the nsp7 to nsp8 and a second one of approx. 950 Å2 connects the dimers and form the observed heterotetramer. Interestingly, analysis of the surface electrostatic potential revealed a putative RNA binding site that is formed only within the heterotetramer.
Keywords: virové nestrukturální proteiny; Protein Conformation; Crystal structure; multiproteinové komplexy; DNA-primasa; Models, Molecular; Primase; vazebná místa; Coronavirus RNA-Dependent RNA Polymerase; Crystallography, X-Ray; Protein Multimerization; Betacoronavirus; DNA Primase; molekulární modely; SARS-CoV-2; RNA; krystalografie rentgenová; Binding Sites; koronavirová RNA-replikasa; konformace proteinů; multimerizace proteinu; Viral Nonstructural Proteins; Multiprotein Complexes